HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN KECEMASAN DALAM MENGHADAPI DUNIA KERJA PADA MAHASISWA AKHIR DI UNIVERSITAS NUSA CENDANA KOTA KUPANG - Lodia Carolina Hermanus,; Sri Aryanti Kristianingsih, (Jurnal Cakrawala Ilmiah, 2023)
The purpose of this stuy was to determine the relationship between social and anxiety in facing the world of work in final students at Nusa Cendana University, Kupang, totaling 38 respondets. Data collection was carried out using a scale of social support and anxiety in facing the world of work. The result showed that there was no significant relationship between social support and anxiety in facing the world of work for students with a value of r = 0,931 and significant = 0,003 (p<0,05) so it can be concluded that social support has no significant effect on student anxiety in facing the world of work.